Inducing the Solid–Liquid Conversion of Zinc Metal Anode in Alkaline Electrolytes by a Complexing Agent. (1st September 2022) - Wu, Wanlong; Yang, Xianpeng; Wang, Kuo; Lin, Zirui; Shi, Hua‐Yu; Sun, Xiaoqi
Abstract: Primary alkaline aqueous batteries with Zn metal anodes have been commercialized and show great promise for secondary batteries. However, Zn undergoes a solid–liquid–solid reaction among Zn, Zn(OH)4 2−, and ZnO in alkaline electrolytes, and the insulating ZnO formed on the surface easily passivates Zn underneath. Herein, a complexing agent of Br − is added into the KOH electrolyte. Zn is oxidized to Zn–Br complexes instead of Zn(OH)4 2− during discharge, the former of which exhibits higher solubility. Therefore, Zn undergoes a solid–liquid reaction, and the passivation by ZnO is effectively avoided. Zn is reversibly deposited during charge to form a flat surface on the electrode. Thanks to the excellent kinetics and reversibility of the solid–liquid conversion process, the symmetric cell exhibits a polarization voltage of ≈8 mV at 1 mA cm −2 and only increases to 36 mV at 10 mA cm −2 . The cycle life is extended to 900 h at 1 mA cm −2 and 0.5 mA h cm −2, which is 22× of the one in the KOH electrolyte. The KOH/KBr electrolyte is also applicable to a Zn||MnO2 battery, which delivers 92.5% capacity retention after 500 cycles. This study presents an effective strategy to uncover alternative reaction paths for zinc electrode in rechargeable batteries. Abstract : A complexing agent is introduced into alkaline zinc batteries. Zn is oxidized to Zn‐Br complexes instead of Zn(OH)4 2− during discharge, the former of which exhibits higher solubility. Therefore, Zn undergoes solid–liquid conversion and the passivation by ZnO is avoided. Zn is re‐deposited to form a flat surface during charge. This reaction path significantly enhances the electrochemical performance of the Zn electrode.